Pengaruh sustainability reporting terhadap nilai perusahaan dengan kinerja keuangan sebagai variabel intervening - Rochimah Yulianty; Trinandari prasetya nugrahanti (Sekolah Pascasarjana Perbanas Jakarta, 2020)
This study was conducted to determine the effect of Sustainability Reporting from Economic, Environmental, and Social Aspect on Corporate Value using Tobin's Q measurement with Financial Performance with Liquidity, Activity, Solvency, Profitability, and DuPont System proxies as intervening variable. The sampling technique used is purposive sampling. Data obtained from the IDX & company website of the published sample. Samples obtained 37 companies.Analytical techniques used are multiple linear regression and path analysis. Hypothesis test using t-statistic to test partial regression coefficient and f statistic to test influence together with level of significance 5%. The result of this research stated that Sustainability Reporting Economic aspect has significant positive influence to Profitability, DuPont, and Corporate Value but not significant to Liquidity. Whereas in Activity and Solvability have no significant negative effect.The Effect of Sustainability Reporting Environmental aspect has a significant positive effect on Profitability but not significant to Liquidity. While the negative influence is shown in Activity, DuPont and Solvency significantly and not significantly to Corporate Value. The Effect of Sustainability Reporting on Economics has a significant positive effect on Activity, Solvency, and DuPont. While the negative influence is not significant indicated on Liquidity, Profitability and Value Company. Among the 3 independent variables are Economics, Environment, and Social Economics only which significantly affect the Company Value through Liquidity, Activity, Solvency, Profitability, and DuPont System.